Buyer–seller relational engagement and seller brand equity. Issue 8 (9th December 2019) - Dwivedi, Abhishek; Miles, Morgan; Oczkowski, Eddie; Weerawardena, Jay; Johnson, Lester W.; Wilkie, Dean
Abstract : Purpose: Relational engagement is offered as a framework to describe how buyers and sellers conduct exchange. Relational engagement is conceptualized as a higher-order construct comprising three dimensions: legal bonds, knowledge exchange and co-production. This paper aims to examine the efficacy of the construct by testing its influence on buyer–perceived seller brand equity. Design/methodology/approach: An online survey of 401 US-based industrial buyers was conducted. Data were analyzed using structural equation modeling. Findings: Empirical analysis supports the proposed conceptualization of relational engagement, as well as its influence on seller brand equity through influencing buyer-perceived relationship effectiveness. Practical implications: Relational engagement offers a template to sellers for engaging organizational buyers. A relational engagement strategy has favorable implications for seller brand equity. Originality/value: Relational engagement offers a comprehensive strategic perspective on inter-organizational exchange, moving beyond tactical approaches. The framework reflects the continuum of exchange, incorporating transactional-dominant and relationship-dominant forms of inter-organizational marketing practices.